Six-Month Outcome of Immunocompromised Patients with Severe Acute Respiratory Distress Syndrome Rescued by Extracorporeal Membrane Oxygenation. An International Multicenter Retrospective Study - Schmidt, Matthieu; Schellongowski, Peter; Patroniti, Nicolò; Taccone, Fabio Silvio; Reis Miranda, Dinis; Reuter, Jean; Prodanovic, Helène; Pierrot, Marc; Dorget, Amandine; Park, Sunghoon; Balik, Martin; Demoule, Alexandre; et al. (American journal of respiratory and critical care medicine, 2018)
Rationale: Because encouraging rates for hospital and long-term survival of immunocompromised patients in ICUs have been described, these patients are more likely to receive invasive therapies, like extracorporeal membrane oxygenation (ECMO).Objectives: To report outcomes of immunocompromised patients treated with ECMO for severe acute respiratory distress syndrome (ARDS) and to identify their pre-ECMO predictors of 6-month mortality and main ECMO-related complications.Methods: Retrospective multicenter study in 10 international ICUs with high volumes of ECMO cases. Immunocompromised patients, defined as having hematological malignancies, active solid tumor, solid-organ transplant, acquired immunodeficiency syndrome, or long-term or high-dose corticosteroid or immunosuppressant use, and severe ECMO-treated ARDS, from 2008 to 2015 were included.Measurements and Main Results: We collected demographics, clinical data, ECMO-related complications, and ICU- and 6 month-outcome data for 203 patients (median Acute Physiology and Chronic Health Evaluation II score, 28 [25th-75th percentile, 20-33]; age, 51 [38-59] yr; PaO2/FiO2, 60 [50-82] mm Hg before ECMO) who fulfilled our inclusion criteria. Six-month survival was only 30%, with a respective median ECMO duration and ICU stay of 8 (5-14) and 25 (16-50) days. Patients with hematological malignancies had significantly poorer outcomes than others (log-rank P = 0.02). ECMO-related major bleeding, cannula infection, and ventilator-associated pneumonia were frequent (36%, 10%, and 50%, respectively). Multivariate analyses retained fewer than 30 days between immunodeficiency diagnosis and ECMO cannulation as being associated with lower 6-month mortality (odds ratio, 0.32 [95% confidence interval, 0.16-0.66]; P = 0.002), and lower platelet count, higher Pco2, age, and driving pressure as independent pre-ECMO predictors of 6-month mortality.Conclusions: Recently diagnosed immunodeficiency is associated with a much better prognosis in ECMO-treated severe ARDS. However, low 6-month survival of our large cohort of immunocompromised patients supports restricting ECMO to patients with realistic oncological/therapeutic prognoses, acceptable functional status, and few pre-ECMO mortality-risk factors.
Keywords: hematological malignancies; immunodeficiency; extracorporeal membrane oxygenation; outcome; acute respiratory distress syndrome